The effect of purple sweet potato flour and brown rice substitution on the quality of sourdough bread - Irma Sarita Rahmawati; Farah Salasabila; Nadia Gita Fernanda; Firdaus Sukma; Rahmawati Indira Lahita (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The high dependence on wheat flour and the increasing demand for functional foods for individuals with Diabetes Mellitus have spurred innovations in food products, including sourdough bread. This study aimed to evaluate the effect of substituting 50% of wheat flour with varying ratios of purple sweet potato flour and brown rice flour on the sensory characteristics, proximate composition, and antioxidant activity of sourdough white bread. A Completely Randomized Design (CRD) was employed with four formulations: P0 (control/100% wheat flour), P1 (50:40:10), P2 (50:30:20), and P3 (50:20:30), each with three replications. Analyses included proximate composition (protein, fat, moisture, ash, carbohydrates), sensory attributes (color, aroma, taste, texture, overall acceptance), and antioxidant activity using the DPPH method. The results showed significant differences (p<0,05) between the treatments and the control across all evaluated parameters. Based on the Zeleny test, the optimal formulation was P3, with protein content of 7,51 g, carbohydrate content of 48,86 g, and antioxidant activity (IC50) of 195,39 mg/mL. In conclusion, although the antioxidant activity was classified as weak, the bread formulation remains a promising candidate for functional food targeted at individuals with diabetes. It is recommended that 1,5 slices (approximately 50 g) of this sourdough bread be consumed as a snack for individuals with Diabetes Mellitus.